A comparative study of three akirin genes from big belly seahorse Hippocampus abdominalis: Molecular, transcriptional and functional characterization. Issue 74 (March 2018) - Pavithiran, Amirthalingam; Bathige, S.D.N.K.; Kugapreethan, Roopasingam; Priyathilaka, Thanthrige Thiunuwan; Yang, Hyerim; Kim, Myoung-Jin; Lee, Jehee
Abstract: Akirins, members of the NF-κB signaling pathway, are highly conserved nuclear proteins, which regulate gene expression in many physiological processes, including immunity, myogenesis, carcinogenesis, and embryogenesis. The akirin family in teleost fish consists of two to three genes. In the present study, three akirin genes from Hippocampus abdominalis were identified from a transcriptome database and designated as HaAkirin1, HaAkirin2(1), and HaAkirin2(2) . The nuclear localization of HaAkirin1 and HaAkirin2(1) was confirmed by subcellular localization analysis. In contrast, diffused localization of HaAkirin2(2) was identified in the nucleus and cytoplasm that confirmed the aberrant nature of the nuclear localization signal. Phylogenetic analysis revealed a closer relationship of HaAkirins with other known teleost akirins. All three HaAkirin transcripts were ubiquitously expressed in all examined tissues with higher expression in ovary tissue. Immune challenge with LPS, poly I:C, and Streptococcus iniae exhibited a significant increase in the expression of all three HaAkirins in kidney and liver tissues. NF-κB luciferase assays revealed that relative luciferase activity was significantly higher for all three HaAkirin genes than mock controls. These results suggest that HaAkirin genes might play a role in regulating NF-κB dependent immune gene expression and their expression could be induced by bacterial and viral pathogen recognition molecular patterns. Highlights: Three akirin genes ( Haakirins ) were identified from Hippocampus abdominalis . The loss of second nuclear localization signal was identified in Haakirin2(2). All three Haakirins were prominently expressed in gonadal tissues. All three Haakirins were upregulated after challenging with LPS, poly I:C, and S. iniae. The expression of NF-κB reporter gene was induced by all three Haakirins.